Enhanced catalytic activity and stability of SO2-4/ZrO2 solid acid catalyst combined with carbon nanotubes. Issue 9 (November 2015) - Zhao, Qiang; Meng, Shuangming; Wang, Junli; Qiao, Yongsheng; Li, Zuopeng; Guo, Yong
Abstract: SO 4 2 − / ZrO 2 -carbon nanotubes (CNTs) were prepared through direct precipitation using ZrOCl2 ·8H2 O and H2 SO4 as raw materials and CNTs as support. The structure of composite samples was characterized through X-ray diffraction, scanning electron microscopy, energy-dispersive spectrometry, and Fourier-transform infrared spectroscopy. Results show that CNTs may provide large surface areas and ZrO2 tetragonal was closely coated on CNTs surface. This catalyst was used to synthesize acetophenone ethylene glycol ketal. Factors influencing the synthesis of ketalization were also discussed and optimum reaction conditions were confirmed. Experimental results show that the yield of acetophenone ethylene glycol ketal was approximately 98.5% under optimum reaction conditions.